A Drosophila Model for Screening Antiobesity Agents. (9th May 2016) - Men, Tran Thanh; Thanh, Duong Ngoc Van; Yamaguchi, Masamitsu; Suzuki, Takayoshi; Hattori, Gen; Arii, Masayuki; Huy, Nguyen Tien; Kamei, Kaeko
Abstract : Although triacylglycerol, the major component for lipid storage, is essential for normal physiology, its excessive accumulation causes obesity in adipose tissue and is associated with organ dysfunction in nonadipose tissue. Here, we focused on the Drosophila model to develop therapeutics for preventing obesity. The brummer ( bmm ) gene in Drosophila melanogaster is known to be homologous with human adipocyte triglyceride lipase, which is related to the regulation of lipid storage. We established a Drosophila model for monitoring bmm expression by introducing the green fluorescent protein ( GFP ) gene as a downstream reporter of the bmm promoter. The third-instar larvae of Drosophila showed the GFP signal in all tissues observed and specifically in the salivary gland nucleus. To confirm the relationship between bmm expression and obesity, the effect of oral administration of glucose diets on bmm promoter activity was analyzed. The Drosophila flies given high-glucose diets showed higher lipid contents, indicating the obesity phenotype; this was suggested by a weaker intensity of the GFP signal as well as reduced bmm mRNA expression. These results demonstrated that the transgenic Drosophila model established in this study is useful for screening antiobesity agents. We also report the effects of oral administration of histone deacetylase inhibitors and some vegetables on the bmm promoter activity.